Comparison of Lipoprotein (a) and Serum Cholesterol in Offspring of Patients daignosed as myocardial Infarction - Rahim, Salma; Khan, Abdus Sattar; Bangash, Rahim (Journal of Postgraduate Medical Institute, 2011)
the valute of lipoprotein (a) in the prediction of coronary artery disease (CAD) or myocardial infarction (MI), is an established independent risk factor for premature MI. This study was conducted to diagnose offspring at risk. A total of 120 subjects were investigated serum LP (a) and total serum cholesterol were measured by ELISA and serum cholesterol by enzymatic colorimetric (CHOD-PAD) method using standard kits from spincreact, spain. Lp (a) is a strong lipid variable predisposing to CAD.